Relaciones triangulares Estados Unidos, México y Honduras en 1909 - Rodríguez Díaz, Rosario; Reyes Pineda, Olimpia (CIICLA, Universidad de Costa Rica, 2020)
This article studies the mediation attempts of the United States and Mexico in the face of the conflict in Honduras in 1909. At this wartime situation, Mexican representatives exercised cautious and delaying diplomacy in front of Washington's proposal to send military personnel to, along with the U.S. Marines, take over Honduran customs. The analysis is based on primary sources, particularly diplomatic correspondence, and reveals how the Tegucigalpa government sought allies among its continental neighbors to confront the interventionist policy of the United States.